The Brand Ambassadors of Cosmetics Brands and Their Relevance for Generation Z on The Example of the Czech Republic - Wimberská, Andrea; Štěrbová, Ludmila, 1957-; Antonovic, Vladan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This Master thesis aims to answer these research questions “How Generation Z perceives current celebrity brand ambassadors of cosmetics brands, and who they would like to propose as a new representative?” and “What main characteristics of a brand ambassador are important for Generation Z?”. This thesis was created in collaboration with Czech cosmetic brand – Dermacol, which has more than five celebrity brand ambassadors. The first portion of this thesis concentrates on desk research, whereas the second describes the primary research. For the primary research, there were ten interviews conducted among representatives of Generation Z. In the results, the research showed that celebrities ambassadors are not an appropriate method of targeting Generation Z. A new face of a cosmetics brand should be an ordinary person relatable to those who use that brand regularly and has in-depth knowledge about the brand and products. The appearance of this person should be extraordinary and stand out from the crowd. Moreover, this new face should cooperate just with a few brands and act responsibly in public, as well as in society.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses